A tale of two cities: The discursive construction of 'place' in gentrifying East London. (June 2022) - Ilbury, Christian
Abstract: In recent years, the East End of London has been dramatically transformed from a poor, working-class area, to one of the most fashionable neighbourhoods in the world. Adding to a growing body of research which examines the sociolinguistic dynamics of gentrifying neighbourhoods, this article draws on data from two ethnographic projects to examine how young people from the gentrified (i.e. working-class) and gentrifier (i.e. middle-class) communities index place attachment in East London. I demonstrate that for the gentrified community, place attachment is related to the ethnic and cultural genealogy of the immediate, local neighbourhood. Whilst for the gentrifiers, place identity is associated with the cosmopolitan economic and social opportunities of the city. I argue that whilst these communities occupy the same physical neighbourhood, these discourses suggest that they conceptually and socioculturally reside in two very different cities. (Gentrification, place, space, East London)*